Factors Influencing Maize Farmers' Skills on the Success of Maize Farmers in Deli Serdang District - Rizki Hambali Hsb; Zainarti; Nursantri Yanti (Amkop Management Accounting Review (AMAR), 2025)
This study examines the factors that influence the success of maize farmers in Deli Serdang District with a focus on skills, knowledge, and attitudes/actions. The research was conducted in three villages, namely Suka Maju Village, Sampu Cipta Village, and Gunung Tinggi Village. The sampling method used was simple random sampling with a purposive approach. 69 respondents were selected based on the stratified random sampling formula. Data analysis used multiple linear regression with the help of SPSS software. The results showed that the Knowledge variable (X1) had a significant effect on the success of maize farmers, while the Attitude/Action variable (X2) did not show a significant effect. Furthermore, the results of the F test showed that together the two variables did not have a statistically significant effect on the success of farmers.